The Iron Lady: Assessing the Fatima Jinnah’s Role against Ayub Khan’s Dictatorship - Zaheer, Sana; Chawla, Muhammad Iqbal (Annals of Human and Social Sciences, 2023)
Ayub Khan was primarily an autocrat who governed with cruelty and an iron fist. Fatima Jinnah, often referred to as the mother of the nation, reentered active politics and formed a coalition with various political parties. Despite being a woman, she gained the support of religious leaders in opposition to Ayub Khan. This study explores Fatima Jinnah's resistance against Ayub Khan and analyzes the consequences of her actions on the future of Pakistani politics. This study aims to underscore Fatima Jinnah's contributions to the reestablishment of parliamentary democracy, delving into her actions in response to military rule and the subsequent evolution of her stance during the Martial Law era. Additionally, it will shine a light on her significant presidential campaign during the 1965 Presidential Elections. Let’s see how Fatima Jinnah resisted against Ayub and how her efforts to restore democracy ignited hope for future women leaders and paved the way for other democratic forces.